A novel approach to community CPR and AED outreach focused on underserved learner communities - Alexander R. Fisher; Andrew J. Bouland; Robert Zemple; KaSheta J. Jackson; Jack Perkins (Journal of the American College of Emergency Physicians Open)
Abstract Creating a sustainable community cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) program that reaches underserved communities poses a challenge for the emergency medical services (EMS) community. Attendance, funding, and resources have all been linked to struggles surrounding community CPR/AED programs. Through our experience in conducting CPR/AED trainings in underserved regions of eastern North Carolina, we propose a method of effectively utilizing existing organizations and institutions of learning to expand and maintain a sustainable community CPR/AED program. Furthermore, we demonstrate 10 cornerstones in developing relationships within the community to increase attendance and participation in diverse communities.